Expression profiling of genes involved in the development and function of skeletal muscles in Ts1Cje mouse model of down syndrome - Cheah, Pike See; Bala, Usman; Ling, King Hwa (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Down syndrome (DS) is caused by trisomy of human chromosome 21 (HSA21). Motor dysfunction due to hypotonia has limited labour productivity and have significant effects on socio-economic status in DS individuals. Ts1Cje, a mouse model of DS that exhibits muscle weakness was employed, to investigate the expression profile of selected trisomic and disomic genes involved in skeletal muscle structure and function. Methods: Quadriceps and triceps were harvested from the Ts1Cje (C57BL/6) postnatal day 60-70 mice and corresponding wild-type littermates. Total RNA extracted from these tissues was subjected for quantitative expression profiling of three trisomic genes (Itsn1, Synj1 and Rcan1) involved in neurotransmission and six disomic genes (Lamc1, Leprel1, Myl6b, Msn, Pgm5 and Tmod1) essential for maintenance of muscle structure and function. Real-time quantitative PCR method was used for the profiling. Results: Differential gene expression in DS is reflected by 1.5-fold or more increase in the level of expression as predicted by the gene dosage imbalance hypothesis. The analysis showed no significant changes in the expression level of trisomic genes (Itsn1, Synj1 and Rcan1). On contrary, disomic genes, Leprel1 and Pgm5, were upregulated for more than 1.5-fold in DS quadriceps whereas Lamc1, Myl6b and Pgm5 were upregulated for more than 1.5 fold in DS triceps as compared to the wild-type group. Conclusions: Our findings suggest that the dysregulation of Lamc1, Leprel1, Myl6b and Pgm5 genes is associated to muscle weakness seen in Ts1Cje and may play a role in molecular pathogenesis of muscle weakness in DS.